Metode Demonstrasi dalam Logika Al-Fārābī - Lukman Hakim (Himpunan Peminat Ilmu-Ilmu Ushuluddin (HIPIUS), 2017)
This paper tries to analyze the method of demonstation of al-Farabi in his book under title Manṭiq ‘inda al-Fārābī: Kitāb al-Burhān. In the book, al-Fārābī talked about the method of demonstration to get the right conclusion and compatible with the rational proofs. This method is a kind of syllogism which is different from any other syllogisms. This method gives us the rational proofs which are compatible to reality.